Síntese e caracterização de complexos homonucleares e heteronucleares de lantanídeos e bismuto obtidos a partir de citrato de sódio e 1,10-fenantrolina - Oliveira, Handerson Silva Venceslau (2016)
Homonuclear complexes LnCitnH2O (Ln3+ = Eu3+, Tb3+ and Gd3+) were synthesized by stoichiometric addition of the respective aqueous solutions of the Ln3+ ions under the form nitrate and sodium citrate solution (Na3Cit) at a ratio of 1:1. A complex of formula Bi6O4(OH)4Cit2.2H2O, (M1), was synthesized similarly to the homonuclear complexes Ln3+, wherein the composition obtained was not compatible with the stoichiometry of the starting reactants, i.e., the stoichiometric bismuth/citrate ratio of 1:1. Other bismuth complex, with minima formula BiCit2H2O, (M2), was synthesized by reaction of Na3Cit with Bi(NO3)3 and phen, from the stoichiometric ratio 1:1:1, i.e., citrate, Bi3+ and phen. The complex EuCit.1/2(phen).2H2O (phen = 1,10-phenanthroline) was obtained by reaction between Na3Cit, Eu(NO3)3 and phen with a stoichiometry of the starting reactants in the ratio 1:1:1. Complexes bismuth and lanthanide, heteronucleares, were also synthesized in the ratio 1:1:2, from their respective nitrate salts of Bi3+ and Ln3+ and of the Na3Cit salt. All of these materials were characterized using: atomic graphite furnace absorption spectrophotometry, elemental analysis (CHN), (except for complexes M1 and M2), infrared (IR) spectroscopy and thermal analysis (TG-DTA-DTG). For the EuCit.1/2(phen).2H2O complex, luminescence spectroscopy was also used, which showed high luminescent intensity when irradiated with light of wavelength 350 nm. From the quantitative data of the graphite furnace, elemental analysis (CHN) and thermal analysis techniques, the chemical composition of each complex was suggested and by infrared, coordination forms of the ligands Cit and phen to ions metallics were found. For the heteronuclear complexes, the results of all these techniques indicate structures of the types [LnBi2Cit2.3H2O](H2O)3 ( Ln = Eu3+ and Gd3+ ) and [BiTbCit.2H2O](H2O)3.